Polyvinyl Alcohol/SiO2 Hybrid Dielectric for Transparent Flexible/Stretchable All‐Carbon‐Nanotube Thin‐Film‐Transistor Integration. (9th March 2020) - Zhang, Ziwei; Du, Chunhui; Jiao, Haoxuan; Zhang, Min
Abstract: Flexible and stretchable electronic (FSE) transistors create various novel applications. Carbon nanotubes possess high intrinsic mobility and exceptional mechanical and optical characteristics, which lead to a great potential as channel and electrodes in FSE transistors. At the same time, gate dielectric is also required to be intrinsically flexible/stretchable and integratable. However, few high‐performance solutions have been reported. By adopting polyvinyl alcohol (PVA)/SiO2 hybrid layer as dielectric, the integration of high‐performance intrinsically flexible/stretchable carbon‐nanotube‐based thin film transistors is proposed and realized simply by traditional photolithography‐etching and low‐temperature solution processes. The PVA/SiO2 dielectric simultaneously provides a relatively high‐ k value, improves the carrier conduction interface, increases the carbon nanotube (CNT) density, and protects the PVA from plasma damage. Soft transistors with carbon nanotube channel and electrodes exhibit carrier mobility of 14 cm 2 V −1 s −1 within an operation voltage of 0.3 V. These transistors show a small bending radius of 3 mm, and the stretchable transistors can withstand 50% strain with no significant electrical degradation observed, when measured in situ and along different directions for more than 1000 cycles. This work provides a solution for soft transparent transistor integration, indicating promising applicability to soft circuits, displays, and wearable electronics. Abstract : By adopting polyvinyl alcohol/SiO2 hybrid layer as dielectric and adopting carbon nanotubes as channel and source/drain/gate, high‐performance flexible and stretchable thin film transistors are realized simply by utilizing traditional photolithography‐etching and low‐temperature solution processes. The fabricated flexible transistors show a small bending radius of 3 mm, while the stretchable transistors can withstand 50% strain with no significant electrical degradation.